PENGARUH CITRA MEREK DAN MOTIVASI BELANJA HEDONIS TERHADAP PEMBELIAN IMPULSIF ONLINE DI INSTAGRAM - Mirza Putri Andita; Umari Abdurrahim Abi Anwar (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The existence of social media makes Indonesian women easy to get information about well-known global fast fashion brands such as Zara. This condition triggers them to buy Zara clothes impulsively on online platforms such as Instagram. The purpose of this research to determine the effect of Zara’s brand image in the minds of consumers and the factors that motivate them to do hedonic shopping such as adventure, ideas, relaxation, and shopping value on their desire to do impulse buying on Instagram. The data was obtained by distributing questionnaires to 108 respondents who had bought 1 (one) Zara’s shirt on Instagram in the last 1 year (April 2022 – April 2023). The hypothesis were tested using bootstrapping test in Smart PLS 4.0. The results show there is not a significant effect of brand image on online impulse buying. However, the hedonic shopping motivation has a significant effect on online impulse buying.